The elastoplastic problem of the half-space with a hole subjected to axially symmetric loading - Long, Vu Do (Vietnam Journal of Mechanics, 2005)
The elastoplastic problem of the half-space with a hole subjected to axially symmetric loading considered in this paper is based on the elastoplastic deformation process theory. Solution of this problem is carried out by using the modified elastic solution method and the finite element method. Some results of numerical calculation are presented here to give the picture of plastic domains enlarging in the body and the obtained displacements on the free boundary of the half-space.